REGULATIONS FOR E-COMMERCE AGREEMENT ACCORDING TO ICT ACT AND TITLE III OF INDONESIAN CIVIL CODE - Ery Agus Priyono; Budiharto Budiharto; Asri Hayyunniarizka Wulandari (Fakultas Hukum, Universitas Diponegoro, 2019)
As a fruit of technological telecommunication prowess that is the internet, e-commerce has unveil the barrier that obstructs economic growth due to the unnecessarily complicated conventional procedures of bureaucracy. Technological deveopment in telecommunication has a great contribution to the economic growth for which we should be thankful. Yet at the same time, it needs to be regulated in order to construct a condusive and viable climates for economic growth. This article intends to disclose the availability of regulations that can ensure the safety and stability of the economy and keep the investors, consumers and entrepreneurs in accordance with the Title III of Indonesian Civil Code. The research method of this paper is normative approach that is based on secondary data. The outcome of the research is we found out that e-commerce practices shall be subjected under paragraphs 1320, 1321, 1337, 1338 and 1339 of Indonesian Civil Code.